From Fabric to Finish: The Cytotoxic Impact of Textile Chemicals on Humans Health - Vera Machado; Andréa Marinho; Paula Vieira de Castro; Teresa Silva (Textiles, 2025)
Humans are in constant contact with clothing and textiles throughout their lives, which can expose them to chemicals present in these materials. Chemicals used in fiber production and in material processing can be absorbed through the skin, ingested, or inhaled, causing allergic reactions. Advancements in modern textiles have made them more versatile and functional for a variety of applications, resulting in the use of more chemicals. Regarding the textile industry, several studies have focused on the environmental impact of its effluents and dyes, and, more recently, several studies have focused on textile waste impact in general. Nevertheless, few studies have been carried out on human cytotoxicity, and very little is known about the dangers of long-term use of textiles. The aim of this work was to review the literature to understand what has been done in the field of textile cytotoxicity. In addition, this work also highlights the existing gap regarding regulation and standardized tests for the analysis of everyday clothing. There is an urgent need to establish regulations and standardize testing protocols to assess the potential cytotoxic effects that may arise from finished textile products before they are marketed, in order to guarantee consumer safety.